Spatial and Frequency Compounding in Application to Attenuation Estimation in Tissue - KLIMONDA, Ziemowit; LITNIEWSKI, Jerzy; KARWAT, Piotr; NOWICKI, Andrzej (Archives of Acoustics, 2015)
The soft tissue attenuation is an interesting parameter from medical point of view, because the value of attenuation coefficient is often related to the state of the tissue. Thus, the imaging of the attenuation coefficient distribution within the tissue could be a useful tool for ultrasonic medical diagnosis. The method of attenuation estimation based on tracking of the mean frequency changes in a backscattered signal is presented in this paper. The attenuation estimates are characterized by high variance due to stochastic character of the backscattered ultrasonic signal and some special methods must be added to data processing to improve the resulting images. The following paper presents the application ofSpatial Compounding (SC), Frequency Compounding (FC) and the combination of both. The resulting parametric images are compared by means of root-mean-square errors. The results show that combined SC and FC techniques significantly improve the quality and accuracy of parametric images of attenuation distribution.